Characterization of Sugarcane Bagasse–Coconut Shell Biomass Briquettes Using a Damar Resin–Tapioca Starch Composite Binder: Proximate Analysis, Calorific Value, and Combustion Performance - Syamsul Bahri Widodo; Zainal Arif; Satriawan Sagino (Fakultas Teknik Universitas Samudra, 2026)
The utilization of biomass waste as a renewable energy source offers a sustainable approach to reducing dependence on fossil fuels while increasing the economic value of agro-industrial residues. Sugarcane bagasse is widely available but has relatively low energy characteristics, making it necessary to combine it with high-carbon biomass such as coconut shell. This study investigated the effect of different proportions of sugarcane bagasse charcoal and coconut shell charcoal, bonded with a composite adhesive of damar resin and tapioca starch, on the proximate characteristics, calorific value, and combustion performance of biomass briquettes. An experimental method was employed using five charcoal compositions (90:10, 80:20, 70:30, 60:40, and 50:50). Briquette characterization included moisture content, ash content, volatile matter, fixed carbon, calorific value measured using a bomb calorimeter, and combustion performance evaluated by measuring flame, container, water, and ambient temperatures with a K-type thermocouple. The results showed that increasing the proportion of coconut shell charcoal increased the calorific value from 6,561.491 cal g⁻¹ to 7,119.492 cal g⁻¹, and all briquette compositions satisfied the minimum requirement of SNI 01-6235-2000. The 70:30 composition exhibited the highest heat transfer efficiency, whereas the 90:10 composition produced the highest flame temperature. These findings demonstrate the potential of sugarcane bagasse–coconut shell briquettes as a sustainable alternative solid fuel.